ANALISIS PENGUASAAN MENYIMAK HSK LEVEL 4 PADA MAHASISWA ANGKATAN 2016 FKIP UNTAN - Novia, Ieke Endriani; Thamrin, Lily; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractListening is one of the most important parts of learning a language. If you don't master at listening, it might affect other language learning abilities, for example: speaking, reading, and writing. Everyone has a different understanding ability, some people just need to listen once to immediately understand what they heard about, there are also some people who must listen for many times to understand what they heard. Therefore when learning languages, we must increase the listening skills. If you succeed in improving listening skill you will be useful for yourself. To find out the mastery of abilities and difficulties in listening to HSK level 4 in the mandarin language education students at Faculty of Teacher Training and Educationï¼ŒStudy Program Chinese Languageï¼ŒTanjungpura University 2016 generation, the author conducted research on students by using the listening part questions at HSK level 4. The results of the research on true and false questions section is 77.69% answers it correctly; second is multiple choice questions, the percentage that answers correctly is 61.54%. The result of listening HSK level 4 class B is very good, while class A is not so good. Its means class A must study hard Chinese language.Â Keywords: Master, Listening Skill, Hanyu Shuiping Kaoshi Level 4